Hubungan Antara Persepsi Terhadap Kompensasi Dengan Keterlibatan Kerja - Kautsar, Iqlima; Drs. Mohammad Amir, Drs. Mohammad Amir,M.Si (2016)
different individuals will see the same thing in a different way. Work engagement as "a working approach that is designed to ensure that employees are committed to the goals and values of the organization / company, motivated to contribute to the success of the organization / company, and is able at the same time to increase their own sense of well-being". This study aims to: (1) determine the relationship between the perception of compensation with the involvement of Labour, (2) to determine the level of behavior Involvement Work, (3) to determine the impact of compensation on employees, (4) to determine the perception of Compensation for Engagement Work on employees , This study uses Surakarta Muhammadiyah University employee population of 60 subjects were used as samples. Data collection tool that is used to get the data in this study is the scale of the compensation scale with the scale of job involvement. While data analysis technique using Pearson Product Moment. Based on the results of data analysis coefficient obtained korelasir_ (xy) = 0.540 with sig. 0,000; p ≤ 0.01. Thus, it can be said there is a significant positive relationship between compensation and job involvement. Effective contribution perception of compensation with the involvement of labor by 29% and 71% were influenced by other variables. Work engagement is included in the low category with the average of 57.10 and a mean empirical mortgages amounted to 75. The level of perception of compensation medium category with a mean of 79.57 and a mean empirical mortgages by 80. Keywords: Perception, Compensation, Work Engagement